An Introduction to the Securities and Exchange Commission (Book). - Hendrickson, Harvey S.; Eskew, Robert K. (The Accounting Review, 1986)
Reviews the book "An Introduction to the Securities and Exchange Commission," by Larry Gene Pointer and Richard G. Schroeder.